Urban Esthetic Analysis of Bandung City - Damayanti, Verry; Pradifta, Fachmy Sugih; Barwanto, Lutfhi Ahmad; Yoseva, Amalia Putri; Fadhillah, Muhammad Ersyah; Maulana, Galang Rahman (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2024)
The growth and development of the population has caused urbanization phenomena that imply some problems such as congestion, dusty settlements, lack of open green spaces, floods, air pollution, which of course can reduce the comfort and aesthetics that exist in Bandung City. Efforts to improve the aesthetics of the city of Bandung, are currently limited to attempts to set up pavements and parks, as well as underground cable planting systems. (ducting kabel). The aesthetics of a city and its layout can influence the way people see and feel the city, as well as how they interact with its surroundings. Therefore, in order to make an effort to improve the aesthetics of a more targeted city, it is necessary to assess the quality of aesthesia of the city first. Thus, the purpose of this research is to evaluate the aesthetic quality and the efforts to improve the quality of the esthetics of the city in Bandung. The evaluation of the city's aesthetic quality was analysed using the Scenic Beauty Estimation (SBE) method, which assessed 25 vantage points in Bandung. From the results of the SBE assessment , the vantage point with the lowest SBE score is found in the densely populated area of Tamansari (A1) with a score of 0.00 and the highest is the area of Mesjid Al Jabbar (F2) with the score of 227.56.